2011
DOI: 10.1200/jco.2010.32.7114
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Is Effective in Children With Previously Untreated Chronic Myelogenous Leukemia in Early Chronic Phase: Results of the French National Phase IV Trial

Abstract: Imatinib is effective in children with CML in CP with response rates similar to rates reported in adults. The adverse effects are acceptable, but longer follow-up studies are required to fully assess the long-term impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
152
4
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 22 publications
7
152
4
3
Order By: Relevance
“…[3][4][5] Reports in adults indicate that measurement of BCR-ABL1 transcripts 3 months after starting imatinib can predict outcome with better overall survival in patients with a BCR-ABL1/ ABL ratio of ,10% at this time point. 6 In order to address the relevance of this cutoff in the pediatric population in terms of cytogenetic and molecular responses and outcome, we reanalyzed the French Glivec phase 4 study data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Reports in adults indicate that measurement of BCR-ABL1 transcripts 3 months after starting imatinib can predict outcome with better overall survival in patients with a BCR-ABL1/ ABL ratio of ,10% at this time point. 6 In order to address the relevance of this cutoff in the pediatric population in terms of cytogenetic and molecular responses and outcome, we reanalyzed the French Glivec phase 4 study data.…”
Section: Introductionmentioning
confidence: 99%
“…Although imatinib is effective for the majority of children with chronic myeloid leukemia (CML), [1][2][3] 13% to 25% of children have a poor response. [3][4][5] Reports in adults indicate that measurement of BCR-ABL1 transcripts 3 months after starting imatinib can predict outcome with better overall survival in patients with a BCR-ABL1/ ABL ratio of ,10% at this time point.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are similar to those previously reported in CML children treated with IM. [5][6][7] The mechanism by which TKI treatment causes a growth delay in children remains unknown. Recently, Hobernicht et al suggested that the BCR-ABL targeted TKIs resulted in a decreased GH secretion at the pituitary level rather than an impaired action on downstream targets.…”
mentioning
confidence: 99%
“…27,28 However, imatinib can only control and not 'cure' the disease. Furthermore, the long-term (that is, several decades) effects of TKI usage remain unknown.…”
Section: Discussionmentioning
confidence: 99%